The Apothecaries of Catalonia between the XIII-XVIII centuries. A socio-economic and public health vision - Parrilla Valero, Fernando (Ars Pharmaceutica (Internet), 2018)
Introduction: This study tries to give a global vision of the professional task and of the economic, political, social and public health relevance of the Apothecaries of Catalonia, from its constitution, in the XIII century, until its extinction, at the end of the XVIII century. Previously it is necessary to refer to the historical context, the development of public health during the period of study and the origin of the apothecary profession. Objective: To present the evolution of apothecaries in Catalonia during the study period. Methods: Bibliographic review on the evolution of apothecaries in Catalonia, as well as on the development of public health and the historical context during the study period. Results: The development of the apothecary profession in Catalonia can be divided into three distinct stages: the birth of the profession (XIII-XV centuries), the consolidation of the profession (XVI-XVII centuries) and the decline of the profession (XVIII century).